Edukasi Tentang Stunting Pada Balita Dalam Rangka Peningkatan Pengetahuan Pada Ibu Di Desa Tetewatu - Mardiana Ahmad; M. Yamin; Budu; Darmawansyah; Kurniaty; Rinandha Eragradini; Muhammad Akbar Walenna; Nur Aliya Arsyad (Cv. Utility Project Solution, 2022)
Stunting affects about a quarter of children aged < 5 years worldwide. Stunting in children can cause lack of cognitive development, prone to disease and have lower immunity. Children with stunting are affected by malnutrition in the womb and childhood, as well as infections that often occur before or after birth and therefore have a greater risk of getting sick and dying. The lack of maternal knowledge about health and nutrition before pregnancy and the puerperium is one of the causes of stunting. The purpose of community service is to provide health education through counseling about stunting. The method of community service activities is to give material to 100 mothers who have toddlers through lectures and questions and answers. To evaluate the success of the community service activities, an assessment was carried out using a questionnaire, an assessment was carried out before and after providing counseling. The results of community service activities obtained an increase in maternal knowledge, namely 98% who understand about stunting and 2% who do not understand about stunting. It is hoped that with an increase in maternal awareness, it can prevent stunting events.